Modelling and mapping permafrost at high spatial resolution in Wapusk National Park, Hudson Bay Lowlands 1 This article is one of a series of papers published in this CJES Special Issue on the theme of Fundamental and applied research on permafrost in Canada. 2 Earth Science Sector Contribution 20110058. - Zhang, Yu; Li, Junhua; Wang, Xiping; Chen, Wenjun; Sladen, Wendy; Dyke, Larry; Dredge, Lynda; Poitevin, Jean; McLennan, Donald; Stewart, Heather; Kowalchuk, Sheldon; Wu, Wanli; et al. (Canadian Journal of Earth Sciences, 2012)
Most spatial modelling of permafrost distribution and dynamics has been conducted at half-degree latitude/longitude or coarser resolution. Such coarse results are difficult to use for land managers and ecologists. Here we mapped permafrost distribution at 30 m × 30 m resolution for a region in the northwest Hudson Bay Lowlands using a process-based model. Land-cover types and leaf area indices were derived from Landsat imagery; peat thickness was estimated from elevation based on field measurements; and climate data were interpolated from station observations. The modelled active-layer thickness and permafrost extent compared well with field observations, demonstrating that modelling and mapping permafrost at a high spatial resolution is practical for terrains such as these lowlands. The map portrayed large variations in active-layer thickness, with land-cover type and peat thickness being the most important controlling variables. The modelled active-layer thickness on average increased by 37% during the twentieth century due to increases in air temperature and precipitation, and permafrost disappeared in some southern areas. The spatial scale of the permafrost maps developed in this study is close to that of the ecosystem and landscape features; therefore, the results are useful for land management and ecosystem assessment.